(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Enhancing the quality of human resources is the primary goal of the autonomous learning initiative supported by the Minister of Education and Culture. All participants in the schools, including State SD Gunungpring 1 and State SD Gunungpring 2, are learning that the concept of ’Merdeka’ introduces something innovative. Based on a needs analysis conducted with community service partners, priority issues were identified, particularly management challenges related to the inadequacy of AKM (Minimum Competency Assessment) and PPDB (New Student Admission System) under the zoning system. One of the key challenges identified was the lack of teachers’ knowledge in developing independent learning lesson plans (RPP) and employing teaching strategies relevant to the independent learning approach, as well as addressing learning difficulties faced by students. This highlights the need for a thorough understanding of the implementation of the independent learning policy among all stakeholders. State SD Gunungpring 1 and 2 are integrating the independent learning framework to address these policy-related challenges, enabling teachers to effectively implement AKM, manage zoned schools, develop RPPs, and adopt appropriate teaching strategies. The method applied in this community dedication program involved several stages: conducting a needs assessment with commitment partners, delivering lectures and facilitating discussions, preparing materials for accompaniment activities, implementing the accompaniment program, and conducting monitoring and evaluation to ensure the sustainability of the activities. The outcomes of this dedication program were positive. Based on teacher responses, 80% of the teachers successfully participated in the accompaniment sessions, and the program’s success rate reached 80%. It was concluded that most teachers were able to effectively manage school administration, design, and prepare lesson plans. — Program merdeka belajar yang dicanangkan oleh Menteri Pendidikan dan Kebudayaan diarahkan untuk meningkatkan kualitas sumber daya manusia. Merdeka belajar menjadi hal baru bagi seluruh pelaku di sekolah termasuk SD Negeri Gunungpring 1 dan SD Negeri Gunungpring 2. Hasil analisis kebutuhan dengan mitra pengabdian masyarakat ditemukan permasalahan prioritas yaitu permasalahan manajemen meliputi ketidaksiapan AKM dan PPDB menggunakan sistem zonasi. Selain itu, permasalahan prioritas lainnya yaitu permasalahan pembelajaran mencakup kekurangpahaman guru dalam menyusun RPP merdeka belajar dan metode pengajaran yang relevan dengan merdeka belajar. Untuk itu perlu adanya pemahaman dalam mengimplementasikan kebijakan merdeka belajar tersebut bagi seluruh stakeholder salah satunya melalui pendampingan. Pendampingan implementasi merdeka belajar dilaksanakan di SD Negeri Gunungpring 1 dan 2 yang memiliki permasalahan terkait kebijakan baru tersebut. Kegiatan pengabdian ini memiliki tujuan yakni guru di SD Negeri Gunungpring 1 dan 2 dapat mengimplementasi merdeka belajar dengan baik dalam melaksanakan AKM, menerapkan sekolah zonasi saat PPDB, menyusun RPP merdeka belajar, serta menerapkan metode pembelajaran yang tepat dalam merdeka belajar. Adapun metode pengabdian yang digunakan yaitu ceramah dan diskusi dimulai dari menganalisis kebutuhan mitra pengabdian, penyusunan materi kegiatan pendampingan, pelaksanaan pendampingan, serta monitoring dan evaluasi keberlangsungan kegiatan pendampingan. Hasil pelaksanaan kegiatan pengabdian ini berjalan dengan baik berdasarkan hasil angket respon guru yang menunjukkan 80% guru dapat mengikuti pendampingan dan target pencapaian keberhasilan program mencapai 80% sehingga disimpulkan bahwa sebagian besar guru dapat mengikuti pendampingan tentang manajemen sekolah, membuat dan menyusun rencana pembelajaran dengan sangat baik.